Cartão postal de uma baiana (Museu Afro-Digital, 2025)
Collection: Orixás - Fundação Gregório de Mattos
Keywords: Orisha religion; Candomblé; Photographs; Yoruba (African people)--Religion; Yoruba (African people); Yoruba Art